The Existence of Gender-Feminism: Woman Leadership in Historical Momentum of Islamic Perspective in Indonesia - Firdaus, Endis (ASPENSI in Bandung, Indonesia, 2010)
ABSTRACT: Political leadership of woman in Islam in Nusantara (Indonesia) has been existing long time ago. But in Indonesia, its discourse more existed at the end of the 19th century. The strength of current understanding of woman political leadership as a leader (imam) in shalat (praying), it used at home and in the politics area becoming a status quo. The decision of MUI (Majlis Ulama Indonesia or Indonesian Ulema Council) â that forbids a woman to be a President â is not represent an acclamation in a comprehensive collective intellectual voluntary agreement, but the majority. Finally, their opinion has been dissociated by itself from the reality of leadership with division of duty from collective modern political leadership. The division of this duty made the leadership of woman can be realized in the politics area. Therefore, the political leadership of woman in its practical reality doesnât have any resistance taken as forbidden reasons of the woman leadership, both from religion and ideological view.KEY WORDS: gender, feminism, imÄm, woman study, ijtihÄd, and Islamic society in Indonesia.About the Author: Dr. Haji Endis Firdaus is a Lecturer at the Study Program of Islamic Education, Faculty of Social Studies Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. He can be reached at: endisf@yahoo.comHow to cite this article? Firdaus, Endis. (2010). âThe Existence of Gender-Feminism: Woman Leadership in Historical Momentum of Islamic Perspective in Indonesiaâ in TAWARIKH: International Journal for Historical Studies, Vol.1(2) April, pp.211-226. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 1, 2010); Revised (March 5, 2010); and Published (April 28, 2010).